Los creadores de opinión en Francia. - Santos Sáinz, María (Estudios sobre el Mensaje Periodístico, 2000)
During the last years we are attending in France to a excited speech about the Media Elite. Sociologists, politics and also some journalists denounce to the more influences parisiens commentarists to be quiet close to the power and to be staff of the unique thought. But others authors consider that those commentarists are suffering and excessive mediatic fight. While the polemic continue, appears news programs that become exceptional opinion´s creators. The Spitting Images programs it is actually in France one of the opinion platform 93 María Santos Sáinz Los creadores de opinión en Francia because his corrosive sense of humor and his irreverent tone, that has exceeded the traditional critics level of others programs